What we see why we worry why we hope : Việt Nam going forward - Napier, Nancy K. (CCI Press, 2013)
This is an excellent book from which to learn about the real changes happening in Vietnam, a country that is experiencing one of the most rapid economic growth periods in the world, an is undergoing a radical change in its society. The book includes a very vivid description of the "bridge generation" - the generation, a group that bridges the old communist era and the free market era of the current transiton economy.